Reovirus infection of tumor cells reduces the expression of NKG2D ligands, leading to impaired NK-cell cytotoxicity and functionality - Khaleafi, Raghad; Zeleznjak, Jelena; Cordela, Sapir; Drucker, Shani; Rovis, Tihana Lenac; Jonjic, Stipan; Bar-On, Yotam (Frontiers in Immunology, 2023)
In recent years, reoviruses have been of major interest in immunotherapy because of their oncolytic properties. Preclinical and clinical trials, in which reovirus was used for the treatment of melanoma and glioblastoma, have paved the way for future clinical use of reovirus. However, little is known about how reovirus infection affects the tumor microenvironment and immune response towards infected tumor cells. Studies have shown that reovirus can directly stimulate natural killer (NK) cells, but how reovirus affects cellular ligands on tumor cells, which are ultimately key to tumor recognition and elimination by NK cells, has not been investigated. We tested how reovirus infection affects the binding of the NK Group-2 member D (NKG2D) receptor, which is a dominant mediator of NK cell anti-tumor activity. Using models of human-derived melanoma and glioblastoma tumors, we demonstrated that NKG2D ligands are downregulated in tumor cells post-reovirus-infection due to the impaired translation of these ligands in reovirus-infected cells. Moreover, we showed that downregulation of NKG2D ligands significantly impaired the binding of NKG2D to infected tumor cells. We further demonstrated that reduced recognition of NKG2D ligands significantly alters NK cell anti-tumor cytotoxicity in human primary NK cells and in the NK cell line NK-92. Thus, this study provides novel insights into reovirus-host interactions and could lead to the development of novel reovirus-based therapeutics that enhance the anti-tumor immune response.